PENGGUNAAN METAFORA DALAM LIRIK LAGU EBIET G. ADE ALBUM PERJALANAN DAN IMPLIKASINYA PADA PEMBELAJARAN SEMANTIK BAHASA INDONESIA - Tri Mahajani; Sri Rahayu Dwiastuti; Mukodhas Mukodhas (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2017)
ABSTRACTThe research is aimed at describing the use of metaphors and finding out its implications in the song lyrics of Ebiet G. Ade from the album of Perjalanan to semantic learning of Indonesian language. The research uses analytical descriptive method with structuralism and propositional approaches. The technique of data collection is done by using note taking. The data of metaphor is analyzed using content analysis. The result shows that the album of Perjalanan from Ebiet G. Ade, consisting of nine songs, has 40 metaphors used to describe the thought and meaning about love among humans and their life covering happiness, sadness, and imagination. The use of metaphors is also to describe humans, life, feelings, suffering, sadness, and anxiety. Metaphors are also used for describing natural phenomena, societys life, social relations among humans and the description of the world. The description of humans and God relationship is also there, using complex metaphors. The analysis of metaphors use in the song lyrics of Ebiet in the album of Perjalanan can improve students vocabulary enrichment and its meaning. Hence there is an implication to semantic learning of Indonesian language. Keywords: Metaphors, Song lyrics, implication